(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study examines the Islamic economics ecosystem to strengthening Halal SMEs in Indonesia. The empirical analysis is based on a mixed method using SEM-PLS to predict the behavior of muslim SME business owners regarding the halal certification and Analytical Network Process (ANP) to develop a strategy in order to enhance the ecosystem. The result shows that first, halal product assurance has received an adequate position in Indonesian regulation. Second, from SMEs’ perspective, subjective norms regarding Islamic teaching on halal and the ability to analyze the value chain in their business process could increase the willingness to process halal certification but the willingness to extend the certification is probable in the future. Third, from the expert’s perspective, we gained some insight into mapping the halal certification problem and developing an alternative strategy for a better ecosystem. Our findings have important implications for government policy, ranging from better halal certification literation and education to SMEs, enhancing SMEs’ capacity to gain a better understanding of value chain analysis to improve their business value and develop a responsive and accommodative policy regarding the SME’s need, especially for halal certification extension.